Comparison of right ventricular function and clinical outcomes in type 2 diabetes patients with and without obstructive coronary artery disease: insights from a CMR study - Jin Wang; Wei-Feng Yan; Ke Shi; Hua-Yan Xu; Shi-Qin Yu; Ying-Kun Guo; Li Jiang; Yue Gao; Yu-Jiang; Xue-Ming Li; Yuan Li; Zhi-Gang Yang (Cardiovascular Diabetology)
Abstract Background Obstructive coronary artery disease (OCAD) marks a high-risk group within patients with type 2 diabetes mellitus (T2DM), underscoring the need for tailored prevention and management strategies. However, limited data exist on right ventricular (RV) function and clinical outcomes in T2DM patients with versus without OCAD. This study aimed to investigate the differences in RV function and clinical outcomes between these two groups. Methods The study included 246 T2DM patients {141 patients without OCAD [T2DM(OCAD−)] and 105 with [T2DM(OCAD+)]} and 85 control subjects. Cardiovascular magnetic resonance were utilized to assess RV structure, function, and global myocardial strain [including peak strain (PS), peak systolic (PSSR) and diastolic strain rate (PDSR) in longitudinal, circumferential, and radial directions]. The endpoints, which included all-cause mortality, heart failure hospitalization, and overall composite outcome, were evaluated over a median follow-up period of 5.7 (3.1, 6.7) years. We used linear regression to identify determinants of impaired RV myocardial strain and Cox proportional hazards models to evaluate their associations with clinical outcomes. Results RV global circumferential PS (GCPS), longitudinal PS (GLPS) and PSSR (PSSR-L) decreased progressively from control subjects to T2DM(OCAD−) patients, and further to T2DM(OCAD+) patients (all P < 0.05). The presence of OCAD was significantly correlated with impaired GRPS (β = − 0.186), GCPS (β = − 0.121), GLPS (β = − 0.153), PSSR-L (β = − 0.165), and PDSR-R (β = − 0.133) in the context of T2DM. Multivariable Cox regression analysis identified OCAD as an independent predictor of future endpoints, with T2DM (OCAD+) patients showing a 1.91-fold increased risk compared to T2DM (OCAD−) patients (hazard ratio: 1.91; 95% confidence interval: 1.06–3.44; P = 0.031). Conclusions T2DM patients with OCAD showed distinct RV functional impairments and worse long-term outcomes compared to those without OCAD, including more severe RV systolic and diastolic dysfunction and a significantly higher risk of adverse clinical outcomes.